Adenosine Deaminase Acting on RNA (ADAR) Enzymes: A Journey from Weird to Wondrous - Keegan, Liam P; Hajji, Khadija; O'Connell, Mary A (Accounts of chemical research, 2023)
The adenosine deaminase acting on RNA (ADAR) enzymes that catalyze the conversion of adenosine to inosine in double-stranded (ds)RNA are evolutionarily conserved and are essential for many biological functions including nervous system function, hematopoiesis, and innate immunity. Initially it was assumed that the wide-ranging biological roles of ADARs are due to inosine in mRNA being read as guanosine by the translational machinery, allowing incomplete RNA editing in a target codon to generate two different proteins from the same primary transcript. In humans, there are approximately seventy-six positions that undergo site-specific editing in tissues at greater than 20% efficiency that result in recoding. Many of these transcripts are expressed in the central nervous system (CNS) and edited by ADAR2. Exploiting mouse genetic models revealed that transgenic mice lacking the gene encoding Adar2 die within 3 weeks of birth. Therefore, the role of ADAR2 in generating protein diversity in the nervous system is clear, but why is ADAR RNA editing activity essential in other biological processes, particularly editing mainly involving ADAR1? ADAR1 edits human transcripts having embedded Alu element inverted repeats (AluIRs), but the link from this activity to innate immunity activation was elusive. Mice lacking the gene encoding Adar1 are embryonically lethal, and a major breakthrough was the discovery that the role of Adar1 in innate immunity is due to its ability to edit such repetitive element inverted repeats which have the ability to form dsRNA in transcripts. The presence of inosine prevents activation of the dsRNA sensor melanoma differentiation-associated protein 5 (Mda5). Thus, inosine helps the cell discriminate self from non-self RNA, acting like a barcode on mRNA. As innate immunity is key to many different biological processes, the basis for this widespread biological role of the ADAR1 enzyme became evident.Our group has been studying ADARs from the outset of research on these enzymes. In this Account, we give a historical perspective, moving from the initial purification of ADAR1 and ADAR2 and cloning of their encoding genes up to the current research focus in the field and what questions still remain to be addressed. We discuss the characterizations of the proteins, their localizations, posttranslational modifications, and dimerization, and how all of these affect their biological activities. Another aspect we explore is the use of mouse and Drosophila genetic models to study ADAR functions and how these were crucial in determining the biological functions of the ADAR proteins. Finally, we describe the severe consequences of rare mutations found in the human genes encoding ADAR1 and ADAR2.
Keywords: inosin; přirozená imunita; myši; messenger RNA; dvouvláknová RNA; adenosindeaminasa; RNA, Messenger; zvířata; Mice; Humans; Inosine; Adenosine Deaminase; Immunity, Innate; RNA, Double-Stranded; lidé; Animals